2017
DOI: 10.1001/jamaophthalmol.2017.0046
|View full text |Cite
|
Sign up to set email alerts
|

Association of Steroid 5α-Reductase Type 3 Congenital Disorder of Glycosylation With Early-Onset Retinal Dystrophy

Abstract: IMPORTANCE Steroid 5α-reductase type 3 congenital disorder of glycosylation (SRD5A3-CDG) is a rare disorder of N-linked glycosylation. Its retinal phenotype is not well described but could be important for disease recognition because it appears to be a consistent primary presenting feature. OBJECTIVE To investigate a series of patients with the same mutation in the SRD5A3 gene and thereby characterize its retinal manifestations and other associated features. DESIGN, SETTING AND PARTICIPANTS Seven affected indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…31 To confirm the SSBP1 variants to be the most likely disease-associated variants in these individuals, we first excluded all candidate variants occurring in a virtual panel of genes previously shown to be associated with posterior segment disorders or inherited optic neuropathies (https://panelapp.genomicsengland.co. 31 To confirm the SSBP1 variants to be the most likely disease-associated variants in these individuals, we first excluded all candidate variants occurring in a virtual panel of genes previously shown to be associated with posterior segment disorders or inherited optic neuropathies (https://panelapp.genomicsengland.co.…”
Section: Identification Of Mutations In Ssbp1mentioning
confidence: 99%
“…31 To confirm the SSBP1 variants to be the most likely disease-associated variants in these individuals, we first excluded all candidate variants occurring in a virtual panel of genes previously shown to be associated with posterior segment disorders or inherited optic neuropathies (https://panelapp.genomicsengland.co. 31 To confirm the SSBP1 variants to be the most likely disease-associated variants in these individuals, we first excluded all candidate variants occurring in a virtual panel of genes previously shown to be associated with posterior segment disorders or inherited optic neuropathies (https://panelapp.genomicsengland.co.…”
Section: Identification Of Mutations In Ssbp1mentioning
confidence: 99%
“…However, the phenotypic presentations are remarkably different. First, SRD5A3‐CDG patients have specific structural and functional eye defects . Cantagrel et al suggested the existence of an alternative pathway for dolichol synthesis, because residual dolichol was found in SRD5A3‐deficient cells with early truncating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Dolichol‐phosphate‐mannose (Dol‐P‐Man) is the mannose donor for N‐glycosylation, O‐mannosylation, C‐mannosylation, and GPI‐anchor biosynthesis. SRD5A3‐CDG patients present with structural and functional eye abnormalities, cerebellar defects, intellectual disability (ID), and muscle hypotonia . PMM2‐CDG patients have characteristic multivisceral symptoms that are associated with generalized N‐glycosylation abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations